A comparative study of in-vivo wound healing properties of Tithonia Diversifolia. A gray crude extracts to Silver Sulphadiazine in Albino Wistar rats. - Daka, Jimmy J; Nyimbili, Temwani; Mwaba, Grace; Dowati, Gladys; Mwanza, Albert; Siankuku, Munsaka; Banda, Derrick; Tembo, Zebron N; Kayamba, Francis; Banda, Danny; Kalirajan, Arunachalam; Simwatachela, Hyden (Sciences of Phytochemistry, 2024)
One species of flowering plant in the Asteraceae family is Tithonia diversifolia A. Gray (T. diversifolia), which grows as a shrub or weed. Significant anti-infective therapeutic characteristics, such as anti-mycobacterial, antifungal, antibacterial, anti-inflammatory, anti-malaria, and anthelmintic effects, have been discovered in the plant's extracts. Ethnic communities have been using the plant extract to cure wounds. They appear to prefer it above conventional treatments in many circumstances, to the point where their aqueous solution may be smuggled into medical institutions in order to augment the care provided. The purpose of this study was to compare T. diversifolia with silver sulphadiazine's capacity for wound healing. For 72 hours, a 70% ethanol alone and water alone was used to extract the plant. After the extracts dried out, the powder was measured and 10 mL of reconstituted volume was assessed at various concentrations for the purpose of treating wounds. Silver sulphadiazine was used as the positive control and distilled water as the negative control. According to the findings, the aqueous extract had a 48.0% healing rate after 14 days of treatment, ethanol had a 20.0% healing rate, and silver sulphadiazine had a 22.0% healing rate. It is possible to draw the conclusion that the aqueous extract concentration of 0.6 mg/10 mL demonstrated a higher healing percentage than silver sulphadiazine and the ethanol extract.